Infliximab (chimeric anti-tumour necrosis factor alpha monoclonal antibody) versus placebo in rheumatoid arthritis patients receiving concomitant methotrexate: a randomised phase III trial. ATTRACT Study Group. - Maini, R; St Clair, E; Breedveld, F; Furst, D; Kalden, J; Weisman, M; Smolen, J; Emery, P; Harriman, G; Feldmann, M; Lipsky, P (1999)
BACKGROUND: Not all patients with rheumatoid arthritis can tolerate or respond to methotrexate, a standard treatment for this disease. There is evidence that antitumour necrosis factor alpha (TNFalpha) is efficacious in relief of signs and symptoms. We therefore investigated whether infliximab, a chimeric human-mouse anti-TNFalpha monoclonal antibody would provide additional clinical benefit to patients who had active rheumatoid arthritis despite receiving methotrexate. METHODS: In an international double-blind placebo-controlled phase III clinical trial, 428 patients who had active rheumatoid arthritis, who had received continuous methotrexate for at least 3 months and at a stable dose for at least 4 weeks, were randomised to placebo (n=88) or one of four regimens of infliximab at weeks 0, 2, and 6. Additional infusions of the same dose were given every 4 or 8 weeks thereafter on a background of a stable dose of methotrexate (median 15 mg/week for > or =6 months, range 10-35 mg/wk). Patients were assessed every 4 weeks for 30 weeks. FINDINGS: At 30 weeks, the American College of Rheumatology (20) response criteria, representing a 20% improvement from baseline, were achieved in 53, 50, 58, and 52% of patients receiving 3 mg/kg every 4 or 8 weeks or 10 mg/kg every 4 or 8 weeks, respectively, compared with 20% of patients receiving placebo plus methotrexate (p<0.001 for each of the four infliximab regimens vs placebo). A 50% improvement was achieved in 29, 27, 26, and 31% of infliximab plus methotrexate in the same treatment groups, compared with 5% of patients on placebo plus methotrexate (p<0.001). Infliximab was well-tolerated; withdrawals for adverse events as well as the occurrence of serious adverse events or serious infections did not exceed those in the placebo group. INTERPRETATION: During 30 weeks, treatment with infliximab plus methotrexate was more efficacious than methotrexate alone in patients with active rheumatoid arthritis not previously responding to methotrexate.